Study of the chemical composition and content of the bioactive compounds of the peels of the fruits of Cactus and the use of the peels in the manufacture of jam and Kompote (Damascus University Journal of agriculture sciences, 2023)
The consumption and preparation of products manufactured from the fruits of cactus results in large quantities of residues (the peels) that contain a high percentage of moisture and acceptable concentrations of sugars and other nutritional components that encourage the growth of microorganisms, causing environmental pollution as a result of their exposure to microbial and chemical corruption. In an attempt to reduce the negative impact of these wastes on the environment and benefit from them as a source of food, this research aimed to study the possibility of benefiting from the peels of cactus fruits of high nutritional value in the preparation of some traditional food products such as jams and compotes. The ratio of peels to the whole fruit was 43%. As studying the chemical composition of cactus peels, it was found that they contain a high percentage of total carbohydrates (12.60%), ash (0.44%) and fibers (1.43%). As for the protein and fat content of the crusts peels, they were low, reaching (0.21% and 0.12%), respectively. The results of the determination of total Phenols and Vitamin C in the peels of cactus fruits showed their presence in the ratio of 166 mg/100g and 52 mg/100g on wet weight basis, respectively, and the antioxidant activity of the peel components was 47%. The results of sensory evaluation of products prepared from the peels of cactus fruits showed the superiority of jam prepared from apricots and cactus peels over traditional apricot jam in terms of taste, color and texture. The jam prepared from a mixture of cactus and apple peels was more acceptable than apple jam with all sensory characteristics.
Keywords: Cactus; Peels; Chemical Composition; Bioactive Compounds; Jam; Apple; Apricot